The Role of Online Journalism in Tuberculosis Awareness: Insights from Indonesia in the Digital Era - Mustamin, Chanra; Akil, Anshar (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2024)
Tuberculosis (TB) is a contagious disease that remains a global health challenge, including in Indonesia. In the digital era, online journalism plays a crucial role as an educational tool to enhance public knowledge about TB prevention and treatment. This study aims to explore the strategies employed by online media in disseminating information about TB and their impact on public awareness. This research adopts a qualitative approach, utilizing in-depth interviews with healthcare professionals and content analysis of various digital platforms, including news articles, infographics, and educational campaign videos. By analyzing content from various digital platforms and conducting case studies on health education campaigns, this study found that data-driven information dissemination, such as using the latest TB statistics, visual content like infographics that increased public engagement by 25%, and collaborations with healthcare professionals and influencers are effective strategies. The findings reveal a 30% increase in public awareness regarding TB prevention and treatment efforts following digital campaigns. Online media not only serves as an information source but also as a platform that fosters active public participation in TB prevention and treatment efforts. The proposed recommendations include strengthening cross-sector collaborations, such as between media, healthcare professionals, and community organizations, developing interactive multimedia-based content, and enhancing digital literacy through local community training programs. This study is expected to contribute to TB eradication efforts through more effective health education.